Pemanfaatan Potensi Pakan Lokal Dalam Peningkatan Produksi Daging Dan Susu Kerbau Di Desa Sangiang Kecamatan Wera - Wandira, Ica Ayu; dohi, muhammad; yanuarianto, oscar; amin, muhammad; karni, ine; aminurrahman; nano septian, i gede; aryadin putra, ryan; amalyadi, rezki; al gifari, zaid; amalia pratiwi, eva; lailatun nurjanah, luluk; firhamsah, ikhwan (Universitas Mataram, 2025)
This community service program was carried out in Sangiang Village, Wera District, Bima Regency, with the aim of enhancing the use of local feed resources to improve buffalo meat and milk production. Sangiang Village was chosen as the program location due to its relatively large buffalo population and the abundance of local feed resources, which had not yet been optimally utilized by farmers. The activities were conducted using a participatory approach, consisting of program socialization, extension activities on feed management, and hands-on training in processing local feed through fermentation and storage. Continuous monitoring and evaluation were undertaken to ensure the objectives were achieved. The results showed improvements in farmers’ knowledge, skills, and awareness regarding the use of alternative feed resources such as corn stover, cassava leaves, sweet potato leaves, and groundnut straw. Farmers also began adopting the introduced feed processing techniques, enabling them to provide quality feed reserves throughout the year. This program not only strengthened farmers’ technical capacity but also contributed to improved buffalo productivity in terms of daily weight gain and milk yield, while supporting food